PENELUSURAN TEKNIK PENCIPTAAN LAGU ANAK MENGGUNAKAN ESTETIKA KARAWITAN SUNDA - Mustikawati, Irna (Paraguna, 2023)
This research was conducted to find a way or framework for creating children’s songs using Sundanese musical aesthethics of Sundanese Karawitan contained in it are the creation of childrens songs in Sundanee Karawitan notation (Da Mi Na Ti La) with the rules contained in Sundanese karawitan such as the use of Sundanese musical notation, use of tunings, rurupan, as well as Sundanese vocal ornamentation (dongkari/senggol) that will be sung. Simply in a children’s song. This research is a forum for researches to practice directly the courses that researches have taken, namely the Sundanese notation system and song literature. This research uses a qualitative method which uses the researcher as the main instrument by obtaining data through libraries, audio, visual and audio-visual data and taking two stages of work, namely, working in the field (fieldwork), then processing it to the stage of working on a table (deskwork). This research basically aims to increase literacy regarding the creation of children’s songs using Sundanese musical aesthetics. Apart from that, this research aims to find techniques or ways to create children’s songs that use Sundanese musical aesthetics. To obtain tjis framework, the researcher conducted an analysis of childrens songs in Sundanese karawitan as well as interviews and cosultations with these figures before realizing what the researchers had obtained from these figures into a form of song notation. Children use Sundanese musical aesthetics. This research will produce a children’s song that is put into Sundanese notation with the theme that researchers have been looking for, namely “Getting to know Sundanese Karawitan”. More specifically, the resarcharcher created childrens songs by introducing one of the musical instruments found in sundanese karawitan, namely the Sundanese gamelan. This theme aims to increase children’s knowledge of musical instruments and the arts of Sundanese karawitan. Research investigating techniques for creating children’s songs in the pelog style and translated to Sundanese notation.